DIALEKTIKA DEMOKRASI DALAM BINGKAI POLITIK PRIMORDIALISME PILKADA: Studi kasus Masyarakat Kabupaten Sumba Barat dan Kabupaten Sumba Timur - Teka, Silvester Sili (Jurnal Bina Praja, 2020)
The momentum of local elections is difficult to separate from primordial politics in the form of local culture in a region. The factors of ethnicity, ethnicity, religion, and cultural practices and rituals have a significant influence on the substance of holding local elections. This article discusses primordial political methods as part of local democracy in traditional Kedde techniques in West Sumba and the Ata (servant)/Maramba (Tuan) culture. A cultural technique has an impact on local elections. The Kedde culture is a space for politicians to gain electoral support. The Ata/Maramba culture threatens political rights and participation due to extreme patron-client relations because it covers all aspects of life, especially local elections of politics. With this reality, local democracy in the regional elections has further reduced the democratic values ​​put forward by David Beetham, namely public control and political equality. This research aims to open the horizons of local democracy in the context of local elections and is expected to contribute to the evaluation of the implementation of local elections. This research shows that aspects of local traditions and culture and the Ata/Maramba tradition are actually used as a means of gaining electoral support, which in reality is contrary to liberal-style democracy. So, it is suggested to change the format of asymmetric local elections based on socio-cultural which can prevent potential violations.